PERSEPSI MASYARAKAT TERHADAP PERATURAN BUPATI INDRAGIRI HILIR NOMOR 1 TAHUN 2014 TENTANG GERAKAN MASYARAKAT MAGHRIB MENGAJI DI KELURAHAN TEMBILAHAN KOTA KECAMATAN TEMBILAHAN - Hardiyansah, Hardiyansah; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by a problem that arises from observations made by researchers, namely the Regulation of the Regent of Indragiri Hilir Number 1 of 2014 concerning the Maghrib Community Reciting Movement in Tembilahan Sub-District, Tembilahan Sub-District City. The formulation of the problem in this study is how the Community Perception of Indragiri Hilir Regent Regulation Number 1 of 2014 concerning the Maghrib Community Reciting Movement in the Tembilahan Subdistrict, Tembilahan Subdistrict City. The purpose of this study was to find out how Community Perceptions of Regents of Indragiri Hilir Regent Number 1 of 2014 concerning the Maghrib Community Reciting Movement in Tembilahan Subdistrict, Tembilahan Subdistrict City. This research method is quantitative descriptive. The population in this study was the entire community of Tembilahan Subdistrict, Tembilahan Subdistrict, 23,968 people to determine the size of the sample, the authors used cluster sampling. Cluster sampling is a regional sampling technique used to determine the sample if there is an object to be studied or a very broad data source, coupled with a porpusive sampling technique so that the sampling is really appropriate, porpusive sampling is a sampling technique with certain considerations with a total sample of 40 people . Data collected through observation, questionnaires and interviews. Based on the results of the study it can be concluded that the Community Perception of Tembilahan Urban District Tembilahan District Against the Regulation of the Regent of Indragiri Hilir Number 1 of 2014 Regarding the Maghrib Kaji Community Movement or better known as GEMMAR MengJI is good or positive.Key Words: Perception, Indragiri Hilir Number 1 Year 2014